Piezoelectric and dielectric properties of Ti rich (Bi0.5Na 0.5)TiO3-Ba(Ti0.95Zr0.05)O 3 system - Netima Sawangwan (2018)
The variation amount of TiO2 at 1, 3 and 5 mol% was added into 0.93(Bi0.5Na0.5)TiO3-0.07Ba(Ti0.95Zr0.05)O3, (BNT-7BZT) powder. The affect of excess TiO2on ferroelectric properties of BNT-7BZT ceramics were studied. It was found that piezoelectric and dielectric constants as well as dissipation factor largely drop with an increase of TiO2 contents. However, TiO2excess can stabilize the curie temperature and give a first phase transition temperature constantly at 125° C with TiO2more than 1 mol%.